Problem domain oriented approach for program comprehension - Pereira, Maria João (2012)
This paper is concerned with an ontology driven approach for Program Comprehension that starts picking up concepts from the problem domain ontology, analyzing source code and, after locating problem concepts in the code, goes up and links them to the programming language ontology. Different location techniques are used to search for concepts embedded in comments, in the code (identifier names and execution traces), and in string-literals associated with I/O statements. The expected result is a mapping between problem domain concepts and code slices. This mapping can be visualized using graph-based approaches like, for instance, navigation facilities through a System Dependency Graph. The paper also describes a PCTool suite, Quixote, that implements the approach proposed.